Khulʿ: Local Contours of a Global Phenomenon - Sonneveld, Nadia (Islamic law and society, 2019)
Abstract This special issue of Islamic Law and Society takes a close look at contemporary manifestations of an Islamic divorce procedure known as khulʿ. Studying khulʿ is not an easy matter, in large part because it is not exactly clear what khulʿ is. Is khulʿ consensual or non-consensual, judicial or extrajudicial, fault or no-fault based? Does khulʿ result in ṭalāq (unilateral repudiation by a husband), or is it an entirely different form of divorce? Is khulʿ initiated by wives or by husbands? As we will explain below, the answer to all of these questions is “yes,” as khulʿ is all of these things.